Developing Competitive Strategies for Legends of Runeterra using Genetic Algorithm - Balbinot, Ricardo A.; Costa, Lincoln M.; Souza, Alinne C. Corrêa; Souza, Francisco Carlos M. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2024)
Card games have long served as recreational tools across various cultures. This genre has also followed the trends of the digital gaming industry, with numerous games now featuring competitive scenes with substantial prizes, such as Legends of Runeterra. This paper proposes an automatic generator for competitive deck lineups in Legends of Runeterra, assessing extensive match databases using a Genetic Algorithm that evaluates candidate solutions based on three different generation strategies. This study introduces an evaluation function and presents empirical results concerning the effectiveness and efficiency of the approach. The findings indicate that the proposed method is useful and representative in a competitive context for all three addressed generation strategies.